Social-emotional competencies and health-related outcomes of health promotion in upper secondary education: a scoping review of German-speaking countries - Miriam Kerzendorfer-Breithardt (Frontiers in Psychology, 2026)
Background The implementation of health promotion and health-risk prevention programmes in educational contexts can support adolescents’ health, well-being, and psychosocial development. Social–emotional and related psychosocial competencies are key resources for coping, positive health behaviour, and risk-behaviour prevention during adolescence. However, evidence on universal programmes for upper secondary students in German-speaking countries (DACH region) that assess these competencies alongside health outcomes is scarce, and the available evidence remains insufficiently synthesised. This scoping review maps the available evidence from Germany, Switzerland, and Austria. Methods A PRISMA-ScR–conformant scoping review searched PubPsych—including ERIC, PubMed/MEDLINE, and PSYNDEX—and the Green List Prevention registry for studies published between 2011 and November 2025. Eligible studies evaluated universal, manualised, German-language interventions targeting adolescents aged 14–19 years (grades 9–13) in the DACH region, used (cluster-)randomised controlled or quasi-experimental designs, and reported social–emotional learning–relevant outcomes. Data on programme, study, outcome, measurement, findings, and quality characteristics were extracted. Social–emotional and related psychosocial outcomes were classified using the CASEL framework. Findings were narratively synthesised. Results Eleven studies, representing 10 programmes met the inclusion criteria, indicating a limited evidence base. Outcome coverage was uneven: programmes most often assessed self-awareness, self-management, and stress-related outcomes, whereas social awareness, responsible decision-making, broader well-being, mental health, and health-related behavioural outcomes were less consistently assessed. Reported findings were mostly modest and heterogeneous across outcome areas and study designs as well across delivery modes, school contexts, and levels of methodological quality. Conclusion German-speaking countries have a limited and fragmented evidence base on universal upper-secondary health promotion and prevention programmes incorporating social–emotional components. Future research and practice should strengthen the assessment of social–emotional learning outcomes, improve implementation reporting, and examine how these components can be systematically integrated into programmes to promote psychosocial coping resources, well-being, and healthy lifestyles in older adolescents.